Concepções de divisibilidade de alunos do 1º ano do ensino médio sob o ponto de vista da Teoria Apos - Chaparin, Rogério Osvaldo (2010)
This study aims to investigate the students' conceptions of a first year high school on the concept of divisibility of natural numbers. The relevance of this study is the importance that, according to Campbell and Zazkis (1996) and Resende (2007), has the divisibility concepts relevant in the development of mathematical thinking, in research activities at any level of education, identification and pattern recognition, in the formulation of conjectures and especially in solving problems. To achieve this I used as the theoretical APOS Theory to analyze the protocols, Sfard in formulating the idea of design and research Rina Zazkis building activities. To collect the data I have chosen a didactic sequence consists of four activities performed in pairs of first year students of high school I teach at school. These survey results show that students had great difficulty in handling the operation of the division, designing mostly divisibility through actions, algorithms, and procedures. They did not know deduce relations, information, ie, mainly not understand that the representation in prime factors is a very important way to relate the concepts of multiple and divisor. The students were unable to apply the concepts mentioned above in a situation contextualized in a situation of daily life. Thus concludes that it is necessary to give greater emphasis to basic issues of the Elementary Theory of Numbers in the teaching of mathematics